Communicative functionality evaluation of older people - Salazar Martínez, Reinaldo.; Abarca Aguilar, Isabel.; Astete Valdebenito, Mónica.; Carrasco Salazar, Daniela.; Torres Contreras, Ignacia.; Velásquez Castro, Belén.; Veloso Henríquez, Camila. (Universidad de Castilla la Mancha, 2022)
There are several instruments that assess the elderly person, although there is still no one that evaluates communication and the possible modifications that may occur in aging (Dulcey-Ruiz, 2013; Muñoz et al, 2013). For the same reason, a study was developed during the year 2020 whose objective was to conform and validate, through Chilean speech therapists, a communication assessment instrument for the elderly, from the functionality point of view, that is, from the communicative functions and structures, activities of daily living linked to communication and social communicative participation (González et al, 2019). The instrument was constructed based on proposed communication protocols and questionnaires developed in previous research (Salazar, 2015) and existing theory on communication and aging (Juncos et al, 2010; Lojo et al, 2014; López and Rubio, 2014). The study, with a quantitative approach, descriptive scope, non-experimental transectional type, recruited 36 Chilean phonoaudiologists with national representation for a probabilistic sampling to which, through a process of expert validation, they performed the analysis of the battery, in terms of content, category and semantics. As results, it was obtained that 92% of the professionals (33) considered the instrument semantically correct to the Chilean reality, accepting 91% of the items of the battery from the perspective of the content and categories presented. Subsequently, the Lawshe statistical method (Osa et al, 2017) was applied, which allows obtaining the statistical index of content validity, obtaining a quotient 0.91, which indicates that the instrument has a high level of validity, considering that the Lawshe method requires a quotient over 0.6 to validate an instrument. With all the above, it was possible to generate a battery that allows determining the communicative strengths and weaknesses of the elderly. Further research is contemplated, carrying out processes of construct validity and standardization of the instrument.
Evaluación de la comunicación funcional en personas mayores
Keywords: Elderly people; Communicative functionality; Evaluation instrument; Communication